2018
DOI: 10.3390/su10030851
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a Field-Scale Soil and Water Assessment Tool (SWAT) Model with Field Placement of Best Management Practices in Alger Creek, Michigan

Abstract: Subwatersheds within the Great Lakes “Priority Watersheds” were targeted by the Great Lakes Restoration Initiative (GLRI) to determine the effectiveness of the various best management practices (BMPs) from the U.S. Department of Agriculture-Natural Resources Conservation Service National Conservation Planning (NCP) Database. A Soil and Water Assessment Tool (SWAT) model is created for Alger Creek, a 50 km2 tributary watershed to the Saginaw River in Michigan. Monthly calibration yielded very good Nash–Sutcliff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Site-specific conditions and dimensions of agricultural BMPs as well as the tillage practices can be incorporated in the SWAT model which is often beyond the capacity of most other watershed models (Xie et al, 2015). The effectiveness of BMPs using the SWAT model has been explored by researchers worldwide (McGregor et al, 1999;Pandey et al, 2005Pandey et al, , 2009b; Betrie et al, 2011;Zhang and Zhang, 2011;Bossa et al, 2012;Strauch et al, 2013;Rocha et al, 2015;Pare et al, 2015;Lampurlanes et al, 2016;Maharjan et al, 2016;Strehmel et al, 2016;Her et al, 2017;Noor et al, 2017;Merriman et al, 2018;Ni and Parajuli, 2018;Qiu et al, 2018;Wang et al, 2018). These studies revealed that the SWAT model has the ability to evaluate BMPs to reduce NPS pollution (sediment and nutrient load) depending on watershed characteristics, and the type and combinations of applied BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Site-specific conditions and dimensions of agricultural BMPs as well as the tillage practices can be incorporated in the SWAT model which is often beyond the capacity of most other watershed models (Xie et al, 2015). The effectiveness of BMPs using the SWAT model has been explored by researchers worldwide (McGregor et al, 1999;Pandey et al, 2005Pandey et al, , 2009b; Betrie et al, 2011;Zhang and Zhang, 2011;Bossa et al, 2012;Strauch et al, 2013;Rocha et al, 2015;Pare et al, 2015;Lampurlanes et al, 2016;Maharjan et al, 2016;Strehmel et al, 2016;Her et al, 2017;Noor et al, 2017;Merriman et al, 2018;Ni and Parajuli, 2018;Qiu et al, 2018;Wang et al, 2018). These studies revealed that the SWAT model has the ability to evaluate BMPs to reduce NPS pollution (sediment and nutrient load) depending on watershed characteristics, and the type and combinations of applied BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…The Soil and Water Assessment Tool 2012 (SWAT) is used for predicting land management practice effects on water quantity and quality in a basin and could be useful in addressing the water quality issues impacting Lake Atitlan [85,86]. The model could predict where the phosphorus contributing to eutrophication is coming from and the effectiveness of best management practices that can minimize it [87].…”
Section: Soil and Water Assessment Tool (Swat) Assessmentmentioning
confidence: 99%
“…This model used the field-scale methodology, described in companion study Merriman et al [41], except for the differences noted below and in Supplementary Materials A. In this study, the predefined watershed boundary and stream option in the ArcSWAT interface was used to input processed National Hydrography Dataset Plus (NHDPlus) [42] scale subbasins and stream network obtained from a WLEB study developed by Texas A&M University [43].…”
Section: Model Developmentmentioning
confidence: 99%
“…While the hydrology calibration period was eight years (WY2007-2014), the EOF, tile, and water-quality calibration period was 2 years. Additional monitoring data was not available during this modelling exercise, however, incorporating additional years of data would be beneficial to ensure the model calibration included climatic variability [41]. Additionally, the EOF, tile, and water quality calibration was performed during the last two years of the simulation period, which assumes there were no major changes in land use, climate, etc.…”
Section: Model Limitationsmentioning
confidence: 99%